Experimental Study on the Tensile Property of a Novel Oriented Linear Porous Metal - Bin Liu; Xin-gang Wang; Yong Tang; Wei Yuan; Chao-bin Fang; Zhen-ping Wan (Advances in Materials Science and Engineering)
A novel oriented linear porous metal (OLPM) with high porosity was fabricated through solid-sintering method with cutting copper fibers. In this study, tensile experiments were conducted to investigate the fracture process of the OLPM and the effects of porosity and sintering parameters on the tensile properties. The typical tensile stress-strain plot of this material was obtained based on a large number of tensile test results. The plot can be divided into three stages, namely, initial linear elastic stage, plastic deformation stage, and tensile fracture stage. Based on the results, the fracture mechanism of the OLPM was further studied. Moreover, the porosity and sintering parameters were also varied to investigate their influence on the tensile properties. Tensile strength and plastic deformation were found to decrease with increasing porosity ranging from 70% to 90%. A higher sintering temperature produced a higher tensile strength for the OLPM sintered in the temperature range of 700°C–900°C, but the strength decreased at 1000°C. In addition, the extension of holding time could also slightly affect the tensile strength. Finally, the tensile properties of the OLPM are significantly higher than those of commercial porous metal and porous metal fiber sintered sheet.